REVIEW: APPLICATION OF IRRADIATION TECHNOLOGY IN NATURAL RUBBER VULCANIZATION PROCESS - Andri Saputra, S.ST., M.Eng. (BATAN, 2021)
APPLICATION OF IRRADIATION TECHNOLOGY IN NATURAL RUBBER VULCANIZATION PROCESS. A new vulcanization technology is needed in order to eliminate some potential negative impacts of conventional vulcanization such as contain nitrosamines and allergen proteins that are harmful to health, toxic residues of accelerator compound, cannot be done at room temperature, and sulfur crosslinking contribute to acidification impact. One of the advanced technologies that can be used in the processing of polymers, such as natural rubber, is irradiation using gamma rays. This study is descriptive analysis by conducting a literature search from books and journals of national and international reputation. Radiation in latex of natural rubber will cause free radical formation, crosslinking, and chain scission between polyisoprene chains, and also produce mostly H2 gas. For crosslinking, materials with G(S):G(X) ratios <1.00 are preferred. The dose increase till certain dose led to an increase in the cross-link density of the irradiated rubbers, while apparently, the degradation mechanism has occurred for doses greater than optimum doses. The tensile strength at break of radiation vulcanizate has long been presumed to be lower than that of sulfur vulcanizate or peroxide vulcanizate. The approaches for enhancing radiation crosslinking could be defined by incorporation with filler, increasing the possibility of polymer radical recombination, and increasing the amount of polymer radicals.